02.07 Prophylactic treatment with pepitem inhibits onset of collagen induced arthritis and pepitem therapy reduces disease severity. (1st March 2017) - Kemble, Samuel; Croft, Adam P; Desanti, Guillaume; Saghir, Atif; Buckley, Christopher D; McGettrick, Helen M
Abstract : Background: The inappropriate recruitment and retention of T-cells into the joint is a cardinal feature of RA, yet the molecular mechanisms underpinning this remain unclear. We recently showed that patients with Rheumatoid arthritis (RA) have a defect in a newly identified immuno-protective check-point (adiponectin-PEPITEM axis) that normally limits T-cell trafficking during inflammation. Here we examined the therapeutic potential of PEPITEM in a murine model of arthritis. Methods: Collagen induced arthritis (CIA) was trigger in DBA-1 mice by immunisation with bovine type II collagen. Synthetic PEPITEM was administered by daily injections starting at day 21 (prior to disease onset) or at the first signs of inflammation. Disease onset and severity were evaluated daily. Bone morphology and leukocyte infiltration were assessed by microCT, immunohistochemistry, flow cytometry and qPCR. Results: Administration of synthetic PEPITEM prior to disease onset inhibited the development of CIA. We observed a significant reduction in disease incidence, clinical score, leukocyte infiltration and bone erosion when compared to control peptide treated mice. Excitingly, PEPITEM therapy administered at the first signs of inflammation in CIA also reduced clinical score, leukocyte infiltration and bone erosion when compared to control mice. Whilst we observed fewer leukocytes in the synovium, PEPITEM therapy did not alter leukocyte trafficking through the draining lymph node. Interestingly, in both approaches, we detected higher levels of the FOXP3 transcript, and TReg cells, in PEPITEM treated mice than in control animals. Conclusions: This leads to the exciting possibility that targeting PEPTIEM represents a valid therapeutic approach for treating T-cell mediated diseases, such as RA. Funding: This work was funded by a Pfizer I-CRP research grant.